2019
DOI: 10.3920/qas2018.1402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on solubility, surface hydrophobicity and structure of rice bran albumin and globulin

Abstract: The effect of heat treatment on solubility, surface hydrophobicity and structure of rice bran albumin and globulin were characterised. The differential scanning calorimetry (DSC), FT-IR and Raman spectra were used to analyse the effect. The results of DSC analysis showed that albumin denatured after a thermal pre-treatment of 70 °C, while globulin denatured at 90 °C. The solubility of albumin sharply decreased after heat treatment, while the solubility of globulin decreased by up to 100 °C. The results of FT-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Indeed, the total amount of protein in these processed quinoa extracts was lower compared to the raw quinoa (i.e., seeds and grains), with, for example, 1.1% and 5.5% ( m / m ) for extruded and seed V4 quinoa varieties from conventional farming, respectively. Such behaviour can be attributed to the effect of heat and pressure treatments on the reduction in protein solubility, resulting in protein denaturation, oxidation, and aggregation [ 14 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the total amount of protein in these processed quinoa extracts was lower compared to the raw quinoa (i.e., seeds and grains), with, for example, 1.1% and 5.5% ( m / m ) for extruded and seed V4 quinoa varieties from conventional farming, respectively. Such behaviour can be attributed to the effect of heat and pressure treatments on the reduction in protein solubility, resulting in protein denaturation, oxidation, and aggregation [ 14 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The DES protein electrophoresis patterns result implied that choline chloride-glycerol can extract globulin and albumin fractions. Tang et al, [29] reported that the molecular weights of rice bran albumin have bands range 14-33 kDa, while globulin showed bands around 20-50 kDa.…”
Section: Protein Molecular Weight Of Rbpmentioning
confidence: 99%

A Three-Level Factorial Model for Maximising Protein Extraction from Rice Bran with Choline Chloride: Glycerol

Kamalea Amaleena Farhana Kamal Ramlee,
Nik Muhammad Azhar Nik Daud,
Mohd Sharizan Md Sarip
et al. 2024
ARMNE